Respiratory rate (RR) based analysis of the photoplethysmogram (PPG) signal for different physiological conditions and age group - Kazmi, Syed Absar (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The use of physiological signals is relatively recent in the development of human activities recognition. Respiratory rate is one of the most significant parameters used to identify human coronary artery diseases. Nowadays, humans are facing daily life pressure, stress, tension and even several diseases. All these diseases can have implications on human. Until now there is no such system that can monitor the physiological signal that can indicate the states of human health based on age group. In this research, a comprehensive analysis is made to estimate the respiratory rate, conducted based on human activities and age groups. A complete system that integrates processing and acquisition (Arduino) and sensor (Easy pulse sensor) is developed. Two graphical user interface are used to acquire the PPG signal namely are Cool Term and Easy Pulse Analyzer. PPG samples taken from participants during sitting, standing, lying and jogging are analyzed based on indoor environment. Bio-medical tool, Kubios HRV is used to manipulate and analyze PPG signal in terms of time, frequency and non-linear domain. Parametric values were observed are Respiratory rate (RR) and Heart Rate Variability (HRV). The results depict some variations in PPG signal as reflection of different physiological conditions and age groups for subjects under test in terms of RR, high frequency (ranges from 0.15-0.4Hz), low frequency (ranges from 0.04-0.15Hz), LF/HF , SD1, SD2 and SD1/SD2 ratio. It is also concluded that the values of RR, HRV and HF components increases (RR 392.1~775.7, HRV 85.02~967.39 and HF 0.1523~0.3984) during transition process from sympathetic to parasympathetic physiological state. Furthermore, the high frequency components are more dominant in the 20's age group. However, low frequency components are dominant in the 50's age group.